Values-driven marketing and IMC: How can emerging critical success factors from a values driven marketing approach bridge the divide between brand owners and brand implementers in the effective execution and application of IMC? - Jacobsen, Anneleigh (Centre for Film and Media Studies, 2024)
Much has been written about the widening rift between brand owners (“clients”) and external brand implementors (“agencies”) in the context of implementing Integrated Media Communications (IMC). In considering four long-term case studies we found four emerging critical success factors that seem to indicate that a values-driven marketing approach can help bridge the gap between brand owners and brand implementors and support effective IMC implementation. Where previous work has focused on the brand implementor side of the relationship, this research focuses on the brand owner side. Using semi-structured interviews with leadership as well as facilitated group workshops on values and the development of value propositions in order to understand (a) the impact of a valuesdriven approach to brands and marketing on the relationship with brand implementors, and (b) the success factors that were common across all four case studies. The four emerging key success factors found can be summarised as follows: 1. The process and values must be driven by the brand owner 2. The roles, responsibilities, measures and remuneration for each brand implementor must be absolutely clear to all involved, and decided by the brand owner 3. The business must have absolute clarity at all levels on the values and value proposition of the brand 4. The brand owner must prioritise finding the consulting services, advice or support of an experienced marketing expert if they do not have this skill set themselves These insights could form the basis for enabling brand owners to more effectively implement and benefit from the potential of IMC in their businesses, particularly in the SME context where marketing skill sets are less prevalent.